A depth-profiling study on the solid electrolyte interface : bis(fluorosulfuryl)imide anion toward improved K+ storage - Wang, Huanhuan (2021)
The solid electrolyte interface (SEI) significantly affects alkaline metal ion battery performance in terms of reversible capacity, Coulombic efficiency, and cycling stability. However, intrinsic properties of SEI layer in potassium ion batteries (KIBs), including structures, components, formation mechanism, and corresponding K+ storage behavior, are poorly understood. Here, we focus on the effect of electrolyte on SEI formation and K+ storage behavior in self-supported nitrogen-doped graphite foams (NGFs). Two types of organic electrolytes, KPF6 and KN(SO2F)2 (KFSI) salt in EC/DEC solution, were carefully selected and compared in detail to reveal the effect of SEI on the K+ ion storage mechanism. The experimental results, including in situ electrochemical evaluations and depth-profiling XPS analysis, demonstrate that the salts of KFSI result in a more uniform, stable, and thinner SEI layer compared with the SEI induced by KPF6. Particularly, the KFSI-induced SEI is rich in stable and uniformly distributed inorganic species and polycarbonates, whereas the KPF6-induced SEI is mainly composed of instable alkyl carbonates. This could be attributed to the larger FSI– size over PF6– and lower LUMO levels than solvents according to theoretical calculations, which effectively prevent SEI from co-intercalation damage, thus leading to high stability of the as-obtained SEI layer. In general, the above-mentioned features could ensure high reversibility and good cycling stability of the self-supported NGFs electrode in KFSI-based electrolyte.